Does RSPO Certification Increase Smallholder Oil Palm Income? Evidence from Batanghari, Indonesia - Mirawati Yanita; Ira Wahyuni; Dompak MT Napitupulu; Gina Fauzia; Karina Rahmah; Ulidesi Siadari (Agro Bali : Agricultural Journal, 2026)
This study analyzes income differentials between independent oil palm smallholders certified by the Roundtable on Sustainable Palm Oil (RSPO) and non-certified farmers in Maro Sebo Ilir District, Batanghari Regency, Indonesia. Although certification is promoted as a mechanism to enhance smallholder welfare, empirical evidence remains inconclusive, and few studies examine net income differences disaggregated by plant age under uniform price conditions. Primary data were collected from September 2022 to August 2023 from 60 farmers (30 RSPO-certified and 30 non-certified), categorized into two plant age groups: 11–18 years and 19–26 years. Farm income was calculated as total revenue minus total cost and analyzed using independent-samples t-tests. The results indicate that RSPO-certified farmers achieved higher productivity and income despite incurring higher input costs. Average annual incomes among certified farmers reached IDR 25,600,675 and IDR 25,785,872 per hectare for the 11–18 and 19–26-year groups, respectively, compared with IDR 20,144,977 and IDR 20,766,920 among non-certified farmers. Income differences of approximately 27.1% and 24.2% were statistically significant (p < 0.05). The findings suggest that income gains are primarily associated with improved technical efficiency, intensified input use, and institutional support rather than price premiums, and remain contingent upon local market and institutional conditions.